2023
DOI: 10.7717/peerj-cs.1325
|View full text |Cite
|
Sign up to set email alerts
|

Classification of basal stem rot using deep learning: a review of digital data collection and palm disease classification methods

Abstract: Oil palm is a key agricultural resource in Malaysia. However, palm disease, most prominently basal stem rot caused at least RM 255 million of annual economic loss. Basal stem rot is caused by a fungus known as Ganoderma boninense. An infected tree shows few symptoms during early stage of infection, while potentially suffers an 80% lifetime yield loss and the tree may be dead within 2 years. Early detection of basal stem rot is crucial since disease control efforts can be done. Laboratory BSR detection methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Metode Marker based tracking yaitu metode tracking pada AR yang dalam pengoprasiannya menggunakan marker dari objek dua dimensi. Objek tersebut kemudian akan menjadi acuan yang akan dibaca oleh kamera dan dimasukkan kedalam komputer [11], [19]- [21]. Metode Markerless yaitu sebuah metode dalam AR yang tanpa mencetak marker atau penanda untuk menampilkan suatu objek digital yang sudah ditentukan.…”
Section: Pendahuluanunclassified
“…Metode Marker based tracking yaitu metode tracking pada AR yang dalam pengoprasiannya menggunakan marker dari objek dua dimensi. Objek tersebut kemudian akan menjadi acuan yang akan dibaca oleh kamera dan dimasukkan kedalam komputer [11], [19]- [21]. Metode Markerless yaitu sebuah metode dalam AR yang tanpa mencetak marker atau penanda untuk menampilkan suatu objek digital yang sudah ditentukan.…”
Section: Pendahuluanunclassified
“…Cultural practices, such as the use of disease-free planting materials, proper sanitation, and crop rotation, can help prevent the introduction and spread of the Ganoderma pathogen [ 18 , 26 ]. Chemical control methods, including the use of fungicides, can provide some control, but their long-term sustainability and environmental impact need careful consideration [ 27 , 28 ]. Biological control agents have emerged as promising alternatives for Ganoderma management [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques were used to detect pests and diseases in a variety of crops, including coffee [19], wheat [20], citrus [21], cotton [22] and forests [16,23], as summarized in Table 2. Despite the number of various remote sensing approaches that were used to monitor pests and diseases in oil palm plantations [24,25], their application at the UAV platform together with vegetation indices and machine learning techniques is still limited [26,27]. Based on Table 2, it also can be concluded that the same vegetation indices can be used to detect different types of pests and diseases in different types of crops.…”
mentioning
confidence: 99%